Khilafah Dalam Pemikiran Hizbut Tahrir Indonesia: Telaah Reaksi Ortodoksi Islam Terhadap Kapitalisme Global - Sudarman, Sudarman (KALAM, 2017)
Hizbut Tahrir intends to save Muslims from the ideas and systems of government that they value kufr, by rebuilding the state of an Islamic caliphate. Hizbut Tahrir was born in 1953 in al-Quds Palestine and entered Indonesia around 1980, growing mainly through the preaching of large campuses. Hizbut Tahrir as a political party aspires to establish an Islamic State with three characteristics in its system of government, namely, first, the Qur'an and Sunnah as the constitution of the state. Second, the shura government is government based on deliberations within the boundaries of Qur'an and Sunnah. Third, the government in the form of khilafah, where the caliph chosen by Muslims to enforce Islamic law.